Life cycle assessment of fuel ethanol from sugarcane molasses in northern and western India and its impact on Indian biofuel programme. (1st April 2015) - Soam, Shveta; Kumar, Ravindra; Gupta, Ravi P.; Sharma, Pankaj K.; Tuli, Deepak K.; Das, Biswapriya
Abstract: India's biofuel programme relies on the ethanol from molasses for blending into gasoline. Therefore, quantification of GHG (green house gas) emissions and the energy consumed during the process of ethanol production is desirable to help policy makers to take meaningful decisions. In order to establish the environmental impact of the biofuels, LCA (life cycle assessment) is conducted for 1 ton of fuel grade ethanol in the NR (northern region) and WR (western region) of India. Four different allocation approaches, WA (without any allocation), MA (mass allocation), EA (energy allocation) and MPA (market price allocation) are used to distribute emissions and energy consumption between the product and the co-products. Total GHG emissions are from 543.3 (−75.9%) to 8219.8 kg CO2 -eq. (262.7%) in NR and 552.0 (−75.8%) to 7382.4 kg CO2 -eq. (225.6%) with respect to gasoline. Similarly, the NER (net energy ratio) also varies with different allocation approaches and ranged from 0.38 to 3.39 in the NR and 0.48 to 4.23 in WR. Using MA approach, maximum GHG emissions reduction are,  −75.9 and −75.8% and NER, 3.39 and 4.23 in NR and WR respectively indicates the environment and net energy benefits of fuel ethanol. It is observed that MA and EA approaches give more acceptable and real life results. Highlights: LCA of sugarcane fuel ethanol conducted in northern and western region of India. Process wise GHG emissions and energy consumption is calculated. Mass, energy and market price allocation used to distribute emissions and energy consumption between the product and co-products. Mass allocation and energy allocation approaches give the acceptable and real life results. E5 and E10 give significant impact on GHG emission reduction and energy benefits.